Pattern of Female Suicides among Reproductive Age Group in Southern Marathwada Region of India - R.A. Patil; R.V. Kachare; P.S. Dode; R.M. Kamble (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: Suicidal deaths reÁect the prevailing social set up andmental healthstatus of the region. Female suicidal deaths show mirror to the society with regards to universally accepted values of equality and justice. Objective: The current study was conducted with an objective to study the pattern of suicidal deaths in females among reproductive age group. Methodology: The present study is an observational, cross-sectional study conducted in Department of Forensic Medicine at a government tertiary care institutes’ mortuary in which 72 autopsy cases of suicidal deaths in females of reproductive age group were taken out of total 553 autopsies conducted at the mortuary of SRT Rural Government Medical College, Maharashtra during January 2021 to December 2021. Results: The most common cause of death in majority of deaths was Burns (45%) followed by poisoning (26%) and hanging (18%) and drowning (11%). Conclusions: Most of the cases of female suicides can be prevented with timely, evidence-based and often cost-effective interventions. This study shows the pattern of reproductive age female suicide cases in rural areas of an economically backward region in Central India and access to psychiatric counselling and legal remedial measures along with equal opportunities for economic independence, basic education and awareness of rights can help to eliminate the shocking trend.